Liquid Crystal Pancharatnam–Berry Micro‐Optical Elements for Laser Beam Shaping. Issue 23 (8th October 2018) - Jiang, Miao; Yu, Hao; Feng, Xiayu; Guo, Yubing; Chaganava, Irakli; Turiv, Taras; Lavrentovich, Oleg D.; Wei, Qi‐Huo
Abstract: Shaping the intensity profile of a laser beam is desired by various industrial applications. In this paper, a new approach is presented to design and fabricate liquid crystal (LC) micro‐optical elements (MOEs) with engineered Pancharatnam–Berry (PB) phases for beam shaping. By generalizing the Snell's law for spatially variant PB phases, molecular orientation patterns are designed for the liquid crystal MOEs to shape a Gaussian laser beam into flattop intensity profiles with circular and square cross‐sections, with the β parameter varied from 4 to 42. It is demonstrated that such liquid crystal beam shaping MOEs can be fabricated with high throughput and high resolution by using a photopatterning technique based on plasmonic metamasks and that they produce excellent beam quality, no zero‐order light leakage with a beam size from 10 to 600 µm. As the plasmonic metamasks allow for encoding arbitrary molecular orientations, i.e., arbitrary geometric phase profiles, the approaches presented here are widely applicable to large‐scale manufacturing of liquid crystal MOEs for any beam shapes. Abstract : Shaping the intensity profile of a laser beam is desired by plentiful industrial applications. Here a new approach is presented to designing liquid crystal Pancharatnam–Berry micro‐optical elements for shaping Gaussian beams into flattop beams. A fabrication approach for these devices with high throughput and high resolution is also presented, using a photopatterning technique based on plasmonic metamasks.